A cooperative study assessing reproductive performance in sows fed diets supplemented with organic or inorganic sources of trace minerals. Issue 1 (3rd December 2019) - Tsai, Tsung; Apgar, Gary A; Estienne, Mark J; Wilson, Mark; Maxwell, Charles V
Abstract: Sows from three university research facilities ( n = 245) were stratified by parity and initial body weight (BW), and within outcome groups, randomly assigned to fortified corn- and soybean meal-based control or organic trace mineral-supplemented, gestation (3, 339 kcal/kg ME; 0.62% standradized ileal digestible [SID] lysine), and lactation (3, 374 kcal/kg ME; 0.97% SID lysine) diets. Control gestation and lactation diets were supplemented with inorganic trace minerals (120 ppm Zn from ZnO, 30 ppm Cu from CuSO4, and 50 ppm Mn from MnSO4 ), and the experimental diets contained the same total level of minerals but complexed organic trace minerals replaced 50% of the inorganic trace minerals. Sows were fed to condition during gestation and on an ad libitum basis during lactation. Sow BW (breeding, d 110 of gestation, 48 h post-farrowing, and weaning) and feed consumed were recorded. During gestation, control sows tended to gain less weight (60.4 vs. 64.6 kg, P = 0.06) and consumed less feed (263.5 vs. 264.8 kg, P = 0.05), and had poorer Gain:Feed (G:F) (0.27 vs. 0.29, P = 0.04) than sows fed the organic trace minerals. Sow average daily feed intake (ADFI) during lactation was similar ( P = 0.28) between groups (4.93 vs. 4.74 kg for control and treated sows, respectively). Number of pigs born alive (11.4 vs. 10.9, P = 0.24) and weaned (10.2 vs. 9.8, P = 0.18), and pig pre-weaning average daily gain (ADG) (0.27 vs. 0.27 kg/d, P = 0.77) and mortality (13.1 vs. 12.9%, P = 0.92) were similar for control and treated sows, respectively. Results of the current study demonstrate that sows fed diets supplemented with organic trace minerals displayed similar reproductive performance, but improved weight gain and G:F during gestation compared with sows fed inorganic trace minerals.